Theoretical-methodological model for the study of socio-ecological systems in conflict from Marx's critical discourse - LUNA-NEMECIO, Josemanuel (Utopía y Praxis Latinoamericana, 2023)
This article describes the theoretical and methodological design for the issues of socio-ecological systems in conflict (SESC). The model arises from the growing socio-environmental devastation whose production worsened with neoliberalism causing ecological and health implications. Designed from the onto-epistemological perspective of Marx's critical discourse, the model allows studying the genesis, structure, development, and trends of a SESC. The preliminary results obtained in this research confirm that the epistemological and conceptual elements of Marx's critical discourse are functional for the design of an analysis model that allows accounting for the conditions of economic and legal possibility that make the configuration of a SESC possible. In conclusion, the relevance of characterizing SESCs as biosocial spaces in they are a metabolic dislocation of the natural conditions of world geography and human breeding.